المنهج النبوي في التعامل مع مقتضى الحال: دراسة تحليلية للظرف الديني، الأمني والسياسي في ضوء السيرة النبوية - Toure, Abdoul Karim; Mohd Anuar Mamat (Penerbit Universiti Kebangsaan Malaysia, 2018)
The world is changing too fast that affect the people as well as the Muslim societies in dealing with those changes. This study explored on the ways the Prophet Muhammad PBUH dealt with various situations that can be employed as guidance to the Muslim. Historically, his da‘wah can be divided into two phases. First came the stage of weakness in Mecca. Second was the stage of migration to Medina, where Muslim strength were built up and expanded. The Prophet Muhammad PBUH had different approaches in dealing with these phases concerning the issues on religious, political and security. This article is based on the textual analysis of selected issues in al-Quran, major works of Hadith and SÊra literature. Overall, the findings show that Prophet Muhammad PBUH is a wise person who is able to choose and make decision based on present consideration for the benefit of the people and the Islamic country. This article is expected to highlight the Prophet’s ways and approaches in dealing with the situations in order to provide a guidance to the Muslim especially the leaders in the various levels of leadership.